Modulation of Hyaluronan Synthesis by the Interaction between Mesenchymal Stem Cells and Osteoarthritic Chondrocytes - Eliane Antonioli; Carla A. Piccinato; Helena B. Nader; Moisés Cohen; Anna Carla Goldberg; Mario Ferretti (Hindawi Limited, 2015)
Bone marrow mesenchymal stem cells (BM-MSCs) are considered a good source for cellular therapy in cartilage repair. But, their potential to repair the extracellular matrix, in an osteoarthritic environment, is still controversial. In osteoarthritis (OA), anti-inflammatory action and extracellular matrix production are important steps for cartilage healing. This study examined the interaction of BM-MSC and OA-chondrocyte on the production of hyaluronan and inflammatory cytokines in a Transwell system. We compared cocultured BM-MSCs and OA-chondrocytes with the individually cultured controls (monocultures). There was a decrease in BM-MSCs cell count in coculture with OA-chondrocytes when compared to BM-MSCs alone. In monoculture, BM-MSCs produced higher amounts of hyaluronan than OA-chondrocytes and coculture of BM-MSCs with OA-chondrocytes increased hyaluronan production per cell. Hyaluronan synthase-1 mRNA expression was upregulated in BM-MSCs after coculture with OA-chondrocytes, whereas hyaluronidase-1 was downregulated. After coculture, lower IL-6 levels were detected in BM-MSCs compared with OA-chondrocytes. These results indicate that, in response to coculture with OA-chondrocytes, BM-MSCs change their behavior by increasing production of hyaluronan and decreasing inflammatory cytokines. Our results indicate that BM-MSCs per se could be a potential tool for OA regenerative therapy, exerting short-term effects on the local microenvironment even when cell:cell contact is not occurring.